Fe−Ni−N based alloys as rare-earth free high-performance permanent magnet across α'' to L10 phase transition: A theoretical insight. (15th May 2021) - Tuvshin, D.; Tsevelmaa, T.; Hong, S.C.; Odkhuu, D.
Graphical abstract: Abstract: Over the years, simultaneous enhancement of the energy density product and thermal stability of 3 d -only metals, without including heavy metals or rare-earth elements, has been a tremendous challenge in the field of permanent magnetism. In this study, we investigate the structural stability and intrinsic magnetic properties of (Fe 1 - x Ni x ) 16 N 2 ( x = 0 − 1 ) across the α ″ to L 1 0 phase transition using the systematic density-functional theory and Monte Carlo simulations. We theoretically demonstrated an extremely large enhancement in the uniaxial magnetic anisotropy ( K u ), up to 1.8 MJ · m - 3 in the L 1 0 -type (Fe 0.5 Ni 0.5 ) 16 N 2, a value roughly three times those of α ″ -Fe 16 N 2 (0.6 MJ · m - 3 ) and L 1 0 -FeNi (0.68 MJ · m - 3 ). Simultaneously, it is predicted that the resulting L 1 0 -type (Fe 0.5 Ni 0.5 ) 16 N 2 phase is energetically more stable than the α ″ -Fe 16 N 2 phase. Further calculations reveal that in L 1 0 -type (Fe 0.5 Ni 0.5 ) 16 N 2, K u can increase up to nearly 3.9 MJ · m - 3 with additional interstitial N atoms. In conclusion, we predict that the Fe 16 N 2 -based compounds can be effectively used as efficient rare-earth free permanent magnets by simultaneously enhancing their structural stability and energy product ( B H ) max .